Transcending the Borders in Persians of Terzopoulos - İhsan Kerem Karaboğa (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
In this paper, two dimensions of transcending the borders in the theatre of Theodoros Terzopoulos is discussed through the main dynamics of the performance of Persians in 2006. The first of these dimensions, the more easily recognizable and observable, is the political dimension. However, the perception and experience of the political is only possible with the more complex and holistic ontological dimension. In the Persians of Terzopoulos, reconstruction of the text of Aeschylus reveals a de-construction of the body of actors. Thus, the political and ontological dimensions melt into each other and the dialog with the “other” of our own body, our sister and victims of self-deception offers the audience a peaceful and democratic means of communication resulting from shared suffering.